2011
DOI: 10.2967/jnumed.110.084392
|View full text |Cite
|
Sign up to set email alerts
|

ErbB-2 Blockade and Prenyltransferase Inhibition Alter Epidermal Growth Factor and Epidermal Growth Factor Receptor Trafficking and Enhance 111In-DTPA-hEGF Auger Electron Radiation Therapy

Abstract: The intracellular distribution of Auger electron-emitting radiopharmaceuticals is a determinant of cytotoxicity. However, the mechanisms by which these agents are routed through the cell are ill understood. The aim of this study was to investigate how trafficking of 111 In-labeled human epidermal growth factor ( 111 In-DTPA-hEGF) relates to that of the EGF receptor (EGFR) and whether coadministration of agents that modulate EGFR signaling alters the efficacy of 111 In-DTPA-hEGF. Methods: The spatiotemporal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Reilly et al (2006) point out that the radiation-absorbed dose in the nucleus is about 15 times higher when 111 In decays in the nucleus than when it decays in the cytoplasm and about 30 times higher when 111 In decays in the nucleus than when it decays at the cell surface. Good correlation has been found between EGFR expression and 111 In-DTPA-hEGF uptake, nuclear localization and DNA damage and cell killing (Cai et al 2008) and convincing evidence for nuclear localization of 111 In-DTPA-hEGF was shown by the fl uorescence energy transfer (FRET) imaging study of Cornelissen et al (2011b). Further, 111 In-DTPA-hEGF was found to inhibit growth of a breast cancer cell xenograft in athymic mice.…”
Section: Application Of Molecularly Targeted Therapeutics/ Applying Pmentioning
confidence: 89%
See 4 more Smart Citations
“…Reilly et al (2006) point out that the radiation-absorbed dose in the nucleus is about 15 times higher when 111 In decays in the nucleus than when it decays in the cytoplasm and about 30 times higher when 111 In decays in the nucleus than when it decays at the cell surface. Good correlation has been found between EGFR expression and 111 In-DTPA-hEGF uptake, nuclear localization and DNA damage and cell killing (Cai et al 2008) and convincing evidence for nuclear localization of 111 In-DTPA-hEGF was shown by the fl uorescence energy transfer (FRET) imaging study of Cornelissen et al (2011b). Further, 111 In-DTPA-hEGF was found to inhibit growth of a breast cancer cell xenograft in athymic mice.…”
Section: Application Of Molecularly Targeted Therapeutics/ Applying Pmentioning
confidence: 89%
“…Realizing the therapeutic potential of epidermal growth factor signaling in cancer therapy, Reilly ' s group is using another Trojan horse approach to deliver an attack to a cancer cell nucleus in the form of human epidermal growth factor (hEGF) complexed to the Auger emitter, 111 In via DTPA (Cornelissen et al 2011b). In their investigations, the Auger emitter labeled hEGF was developed to target EGFR-overexpressing cancer cells.…”
Section: Application Of Molecularly Targeted Therapeutics/ Applying Pmentioning
confidence: 99%
See 3 more Smart Citations